Pengaruh Elemen Fraud Hexagon dan Karakteristik CEO terhadap Financial Statement Fraud - Ratu Seroja Laras Wangi; Hari Setiono; Nurdiana Fitri Isnaini (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to determine the effect of fraud hexagon elements and CEO characteristic elements, namely external pressure, ineffective monitoring, change in auditor, change in director, frequent number of CEO's picture, collusion, CEO education, and CEO experience on financial statement fraud. This research is quantitative type. The population of this study are health sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling method used purposive sampling and obtained 8 sample companies. This study uses secondary data obtained from the company's financial statements and annual reports. The analysis technique used is multiple linear regression analysis. The results showed that the variables of external pressure, ineffective monitoring, change in director, frequent number of CEO's picture, collusion, CEO education, and CEO experience had an effect on financial statement fraud. While the change in auditor variable has no effect on financial statement fraud